2015
DOI: 10.1007/s11431-015-5833-0
|View full text |Cite
|
Sign up to set email alerts
|

Constructal entransy dissipation rate minimization for helm-shaped fin with inner heat sources

Abstract: A model of three-dimensional helm-shaped body composed of a helm-shaped fin and inner heat sources is built in this paper. For the specified volumes of the body, fin and heat source, the constructal optimizations of the body with single and multiple inner heat sources are implemented. The entransy-dissipation-rate-based equivalent thermal resistance (ETR) is minimized in the optimizations. It shows that for the helm-shaped body with multiple inner heat sources, there exist an optimal ratio of the heat source d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 51 publications
0
2
0
1
Order By: Relevance
“…The analytical solutions of the fins were verified by the numerical solutions and the result showed that the MTR reduction of Y-shaped fin reached 36.37%. Moreover, the cylindrical pin-fin [ 51 , 52 ] and helm-shaped fin [ 53 , 54 ] were also optimized based on different optimization objectives and different guidelines for the fin designs were provided.…”
Section: Constructal Optimizations Based On the Entransy Dissipatimentioning
confidence: 99%
“…The analytical solutions of the fins were verified by the numerical solutions and the result showed that the MTR reduction of Y-shaped fin reached 36.37%. Moreover, the cylindrical pin-fin [ 51 , 52 ] and helm-shaped fin [ 53 , 54 ] were also optimized based on different optimization objectives and different guidelines for the fin designs were provided.…”
Section: Constructal Optimizations Based On the Entransy Dissipatimentioning
confidence: 99%
“…质等过程的优化. Feng等人 [20] 采用 耗散研究舵型翅 片中内热源分布、 扩展翅片的半径等因素对传热的影 响, 发现在最佳的热源距离和翅片半径下热流场中 温度梯度更均匀, 传热结构的等效热阻更低. Gong等 人 [21] 分析了圆柱体热源当量热阻, 发现 耗散最小 的结构热阻更小, 结构体内热源平均温度更低, 导热 效率更高.…”
Section: 耗散理论已应用在热源和热沉分布、 相变和传unclassified
“…[37] Then, the extremum entransy dissipation principle and the minimum entransy dissipation based thermal resistance principle for heat transfer were developed and applied to the analyses and optimizations of many heat transfer processes. [21][22][23][24][25][26][27][28][29][30][31][32][36][37][38][39][40][41][42][43][44] Furthermore, Cheng and Liang [33] and Cheng et al [34] proposed the concept of work entransy, with which the entransy balance equation for thermodynamic cycles can be set up. Then, the concept of entransy loss was developed.…”
Section: Entransy Theory and Entropy Generation Minimizationmentioning
confidence: 99%